Preparation of Organic Zn-Phthalocyanine-Based Semiconducting Materials and Their Optical and Electrochemical Characterization. (2nd May 2013) - Hajri, Amira; Touaiti, Sarra; Jamoussi, Bassem
Abstract : In order to increase the species of organic semiconductors, new Zn-phthalocyanines-based organic materials were synthesized and characterized. The new compounds have been characterized by 1 H and 13 C using NMR, FTIR, and UV-Vis. The absorption, fluorescence, and electrochemical properties were also studied. Green photoluminescence was observed in dilute solutions. In solid thin films, π - π * interactions influenced the optical properties, and redshifted photoluminescence spectra were obtained; red emissions for ZnPAL (647 nm) and ZnPTr (655 nm) were found. By cyclic voltammetry, the electrochemical band gap was estimated to be 1.94 and 1.17 eV for ZnPAl and ZnPTr, respectively. Single-layer diode devices of an indium tin oxide/Zn-phthalocyanine/aluminum configuration were fabricated and showed relatively low turn-on voltages (3.3 V for ZnPAl and 3 V for ZnPTr).